Influencia de los mensajes publicitarios que difunden los canales de televisión lojanos, periodo julio- diciembre 2012. Propuesta alternativa - Veintimilla Valdivieso, Andrea Elizabeth (2015)
Once he determined and defined the subject, it proceeded to approach the issue, which was discussed and noted the construction of advertisements on local television, in front of it is born the following problem: The advertising messages disseminated in Loja television channels affect public goals of the city of Loja? Considering the subject and problem-oriented objectives help fulfill certain research were raised. Each of the targets was verified based on a sample survey of the universe to investigate. This research is descriptive and exploratory nature, it is possible to state the views expressed in the work, for it was used methods: scientific, inductive, deductive and qualitative. Similarly, technical survey and interview allowed to obtain results for hypothesis testing and verification of targets were used. Consequently it came to the following general conclusion: The communication process used in making advertising that keep local television media communication, is not adequate for making a good advertisement. And general recommendation: That the directors of TV channels that carry advertisements (preferably 2D) taking into account the processes of communication so that they are more attractive to the public and more profitable. This was achieved having a broader study of the problem of knowledge; therefore, it was determined the need for demonstrative advertising, allowing media workers properly develop an advertising and marketing message is clear. The proposal contains adequate to formal media, thus ensuring an efficient, effective and appropriate communication strategies work.